Forage availability for moose of young silver birch and Scots pine - Kalén, Christer; Bergquist, J (Forest Ecology and Management, 2004)
Forestry in Sweden suffers from browsing damage caused by large herbivores, mainly moose (Alces alces) and roe deer (Capreolus capreolus). Silviculture affects the availability of forage for these animals, and thus the browsing pressure. A step towards modeling the response of trees or to predict browsing damage is to gain more knowledge on the availability of food in forest stands. Individual gap-models are a genre of computer models widely used in studying forest dynamics. Since few of these models include browsing effects, however, they are of limited use for evaluating the effects that silvicultural strategies have on forage availability and browsing damage. The aim of this study was to collect data useful in developing a model for describing the amounts of biomass of young birch (Betula pendula) and pine (Pinus sylvestris) trees available to moose. Birch and pines trees were harvested and were divided into different biomass fractions (leaves and twigs of different diameters). The distribution of leaf/needle and twig biomass in the crown was recorded by dividing the trees into sections. The results showed the distribution of the crown biomass to be best described by a sinusoidal model. On average, the model described 79 and 86% (pine and birch, respectively) of the variation in the different fractions. A significant relationship was found between the basal area and the amounts of both leaves and twigs of the different fractions. The biomass available for consumption increased with tree height up to a maximum of 0.6 and 1.0 kg per tree (pine and birch, respectively), 4 m in height. The correlations obtained can be used for introducing browsing into existing gap-models. (C) 2003 Elsevier B.V All rights reserved.